The position of mefloquine as a 21st century malaria chemoprophylaxis - Regep Loredana; Adamcova Miriam; Schlagenhauf Patricia; Schaerer Martin T; Rhein Hans-Georg (Malaria Journal, 2010)
Abstract Background Malaria chemoprophylaxis prevents the occurrence of the symptoms of malaria. Travellers to high-risk Plasmodium falciparum endemic areas need an effective chemoprophylaxis. Methods A literature search to update the status of mefloquine as a malaria chemoprophylaxis. Results Except for clearly defined regions with multi-drug resistance, mefloquine is effective against the blood stages of all human malaria species, including the recently recognized fifth species, Plasmodium knowlesi. New data were found in the literature on the tolerability of mefloquine and the use of this medication by groups at high risk of malaria. Discussion Use of mefloquine for pregnant women in the second and third trimester is sanctioned by the WHO and some authorities (CDC) allow the use of mefloquine even in the first trimester. Inadvertent pregnancy while using mefloquine is not considered grounds for pregnancy termination. Mefloquine chemoprophylaxis is allowed during breast-feeding. Studies show that mefloquine is a good option for other high-risk groups, such as long-term travellers, VFR travellers and families with small children. Despite a negative media perception, large pharmaco-epidemiological studies have shown that serious adverse events are rare. A recent US evaluation of serious events (hospitalization data) found no association between mefloquine prescriptions and serious adverse events across a wide range of outcomes including mental disorders and diseases of the nervous system. As part of an in-depth analysis of mefloquine tolerability, a potential trend for increased propensity for neuropsychiatric adverse events in women was identified in a number of published clinical studies. This trend is corroborated by several cohort studies that identified female sex and low body weight as risk factors. Conclusion The choice of anti-malarial drug should be an evidence-based decision that considers the profile of the individual traveller and the risk of malaria. Mefloquine is an important, first-line anti-malarial drug but it is crucial for prescribers to screen medical histories and inform mefloquine users of potential adverse events. Careful prescribing and observance of contraindications are essential. For some indications, there is currently no replacement for mefloquine available or in the pipeline.